Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to find the value of the following sum (if exist):

$$\sum_{n=1}^{\infty}\left(\arctan\left(\frac{1}{4}-n\right)-\arctan\left(-\frac{1}{4}-n\right)\right)$$ where, $\arctan$ represent the inverse tangent function - $\tan^{-1}$.

I tried to use the telescoping series idea and the sequence of partial sums but I couldn't cancel any terms!

share|improve this question
add comment

3 Answers 3

up vote 2 down vote accepted

According to Maple, the value is approximately $0.54228694083149264109$. Maple doesn't come up with a closed form, and neither its "identify" function nor the Inverse Symbolic Calculator come up with anything. Do you have any reason to believe there is a closed form for this number?

share|improve this answer
    
No, I have no idea if it has a closed form or not, or even if the sries converge! But if your answer is correct, that's good. If so, is the answer in radian? I mean, is it like $0.54228694083149264109 =0.003012705226841626 \pi$? –  Cole Dec 7 '12 at 3:28
    
Cole, yes it is in radians, and you should not multiply it by $\pi/180$. Your equation is false. It is much closer to $0.1726\pi$, if you want to write it as something times $\pi$. –  Jonas Meyer Dec 7 '12 at 3:29
    
In fact a closed form solution may be found with some work (c.f. my answer). Perhaps that a more direct solution exists... –  Raymond Manzoni Dec 8 '12 at 10:38
add comment

Consider $$\tag{1}f(x):=\sum_{n=1}^\infty \arctan\left(\left(\frac 14-n\right)x\right)-\arctan\left(\left(-\frac 14-n\right)x\right)$$ and let's rewrite the derivative of $f$ : \begin{align} \tag{2}f'(x)&=\frac 4{x^2}\sum_{n=1}^\infty\frac{1-4n}{(4n-1)^2+\bigl(\frac 4x\bigr)^2}-\frac{-1-4n}{(4n+1)^2+\bigl(\frac 4x\bigr)^2}\\ \tag{3}f'(x)&=\frac 4{x^2}\left(\frac {-1}{1^2+\left(\frac 4x\right)^2}+\sum_{k=1}^\infty\frac{k\sin\bigl(k\frac {\pi}2\bigr)}{k^2+\bigl(\frac 4x\bigr)^2}\right)\\ \end{align} (since the $k=1$ term didn't appear in $(2)$)

But the series in $(3)$ may be obtained from $\,\frac d{d\theta} C_a(\theta)\,$ with : $$\tag{4}C_a(\theta)=\frac {\pi}{2a}\frac{\cosh((\pi-|\theta|)a)}{\sinh(\pi a)}-\frac 1{2a^2}=\sum_{k=1}^\infty\frac{\cos(k\,\theta)}{k^2+a^2}$$ which may be obtained from the $\cos(zx)$ formula here (with substitutions $\ x\to\pi-\theta,\ z\to ia$).

The replacement of the series in $(3)$ by $\,\frac d{d\theta} C_a(\theta)\,$ applied at $\,\theta=\frac {\pi}2$ gives us : \begin{align} f'(x)&=\left(-\arctan\left(\frac x4\right)\right)'-\frac 4{x^2}C_{\frac 4x}\left(\theta\right)'_{\theta=\frac {\pi}2}\\ &=\left(-\arctan\left(\frac x4\right)\right)'+\frac{4\pi}{2x^2}\frac{\sinh\left(\frac{\pi}2 \frac 4x\right)}{\sinh\left(\pi\frac 4x\right)}\\ &=\left(-\arctan\left(\frac x4\right)\right)'+\frac{\pi}{x^2}\frac 1{\cosh\left(\frac{2\pi}x\right)}\\ \end{align}

Integrating both terms returns (with constant of integration $\frac {\pi}2$ since $f(0)=0$) : $$f(x)=\frac {\pi}2-\arctan\left(\frac x4\right)-\arctan\left(\tanh\left(\frac {\pi}x\right)\right)\quad\text{for}\ \ x>0$$ i.e. the neat : $$\tag{5}\boxed{\displaystyle f(x)=\arctan\left(\frac 4x\right)-\arctan\left(\tanh\left(\frac {\pi}x\right)\right)}\quad\text{for}\ \ x>0$$

So that your solution will be (for $x=1$) : $$\boxed{\displaystyle \arctan(4)-\arctan\left(\tanh(\pi)\right)}$$

share|improve this answer
add comment

Only for the convergence: For every $n \ge 1$ we have \begin{eqnarray} a_n:&=&\arctan\left(\frac14-n\right)-\arctan\left(-\frac14-n\right)\\ &=&\arctan\left(n+\frac14\right)-\arctan\left(n-\frac14\right)\\ &=&\int_{n-\frac14}^{n+\frac14}\frac{1}{1+x^2}dx=\frac{1}{2(1+x_n^2)}, \end{eqnarray} with $$ x_n \in \left[n-\frac14,n+\frac14\right] \quad \quad \forall n \ge 1. $$ Therefore $$\tag{1} f(n)\le a_n \le f(-n) \quad \forall n \ge 1, $$ where $$\tag{2} f(z)=\frac{1}{2\left[1+(z+1/4)^2\right]}. $$ It then follows from (1) that the series $\displaystyle\sum_{n=1}^\infty a_n$ converges, and $$ S_1:=\sum_{n=1}^\infty f(n)\le \sum_{n=1}^\infty a_n \le S_2:=\sum_{n=1}^\infty f(-n). $$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.